Upper respiratory tract immunization with Pam2Cys-adjuvanted spike protein vaccine achieves sterilizing protection against SARS-CoV-2 - Stewart, Erica L.; Stockdale, Skye; Johansen, Matt D.; Smith, Lachlan; Alca, Sibel; Maxwell, Joshua W. C.; Nguyen, Duc H.; Miemczyk, Stefan; Zhao, Guanshu; Turville, Stuart; Triccas, James A.; Steain, Megan; et al. (Frontiers in Immunology, 2025)
Injected COVID-19 vaccines protect against severe disease, but do not induce robust mucosal immune responses. Nasal vaccines offer the advantage of local immunity to block viral infection and transmission. Previously we showed immunization of a Pam2Cys-adjuvanted SARS-CoV-2 vaccine to the upper and lower respiratory tracts (URT/LRT) induced protective immune responses in the lungs. However, URT/LRT immunization is not representative of nasal vaccines for clinical use that exclusively target the URT. Here, we show that delivery to only the URT with Pam2Cys and spike protein effectively induced strong SARS-CoV-2 specific immune responses in the nasal mucosa. When delivered in a low volume so that vaccine exposure was limited to the URT, Pam2Cys/spike protein induced local SARS-CoV-2-specific Th17 cells and neutralizing antibodies to a similar level to inhaled vaccination reaching both the URT and LRT. We compared URT versus URT/LRT delivery as booster vaccinations following parenteral immunization and found that URT vaccination concentrated the immune response to the URT rather than the lungs. Importantly, URT immunization or boosting induced sterilizing immunity in K18-hACE2 mice challenged with homologous SARS-CoV-2. Thus, booster vaccination to the URT alone with Pam2Cys/spike achieved robust nasal immunity against SARS-CoV-2 and is a promising strategy for clinical development.